Outcome of Delayed Decompression Surgery for Cauda Equina Syndrome secondary to Lumbar Disc Herniation: A Case Report - SM, Lim; J, Johari; MI, Yusof (IIUM Medical Journal Malaysia, 2019)
Cauda equina syndrome (CES) is a constellation of symptoms which consist of low back pain, sciatica, saddlearea paraesthesia, urinary or faecal incontinence, with or without motor weakness, and sensory deficit. Surgical decompression is indicated as soon as possible, as decompression within 48 hours from onset allows maximum improvement of symptoms. Recovery usually occurs months or years postoperatively. We report a case of a patient with cauda equina syndrome secondary to massive lumbar disc herniation who had undergone urgent decompression one week after onset of urinary and bowel dysfunction. The clinical outcome post surgery was also discussed.